1985
DOI: 10.1104/pp.77.3.571
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Pea Chloroplast Pyruvate Dehydrogenase Complex

Abstract: The pyruvate dehydrogenase complex has been purified 76-fold, to a specific activity of0.6 umoles per minute per milligram protein, beginning with isolated pea (Pisum sativum L. var Little Marvel) chloroplasts. Purification was accomplished by rate zonal sedimentation, polyethyleneglycol precipitation, and ethyl-agarose affinity chromatography. Characterization of the substrates as pyruvate, NAD', and coenzyme-A and the products as NADH, C02, and acetyl-CoA, in a 1:1:1 stoichiometry unequivocally established t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…attributable to the chloroplast isoform of PDC that does not undergo reversible phosphorylation (10,11) and is not inactivated in the light (data not shown). Details of this calculation were described by Budde and Randall (7).…”
Section: Mitochondria Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…attributable to the chloroplast isoform of PDC that does not undergo reversible phosphorylation (10,11) and is not inactivated in the light (data not shown). Details of this calculation were described by Budde and Randall (7).…”
Section: Mitochondria Isolationmentioning
confidence: 99%
“…Plants are unique in having an additional isoform of PDC in their plastids (10,11) that is also quite sensitive to product feedback regulation but does not undergo regulation by reversible phosphorylation (10,27). In vitro studies of the PDC kinase have also shown that the phosphorylation-inactivation reaction is stimulated by micromolar NH4+ (29) and is inhibited by pyruvate, the substrate for the PDC (26,30).…”
mentioning
confidence: 98%
“…56 The quaternary structure and organization of the plastid PDC is largely unknown because the plastid PDC, unlike the mitochondrial form, dissociates rapidly in vitro. 57 The presence of all four subunits in the membrane-depleted 30k × g fraction characterized here (bands [17][18][19][20][21][25][26][27] indicates this complex can be isolated under rapid extraction conditions for further structural analyses (Table 2). Since this complex sedimented at relatively low centrifugal forces association with other enzymes is possible and may signal the presence of a larger, metabolic enzyme assembly in plastids including the heteromeric acetyl-CoA carboxylase ( Table 2).…”
Section: Phinney and Thelenmentioning
confidence: 99%
“…Why chloroplasts should contain a GR preferring NADH is at present unclear, although it is already known that chloroplasts contain at least one enzyme that can generate NADH, i.e. pyruvate dehydrogenase complex (3).…”
Section: Discussionmentioning
confidence: 99%